2017
DOI: 10.1111/den.12957
|View full text |Cite
|
Sign up to set email alerts
|

Two penetrating vessels as a novel indicator of the appropriate distal end of peroral endoscopic myotomy

Abstract: TPVs appears to be a simple and reliable indicator to determine the appropriate distal end of myotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 18 publications
0
27
0
2
Order By: Relevance
“…Because POEM is carried out from inside the esophagus, it is more difficult to determine whether the surgery is being done on the gastric side, compared with Heller myotomy. As a result of this, the techniques below are used to verify that the surgery is proceeding on the gastric side . The double‐scope method is particularly useful because it allows direct vision to verify that the myotomy extends down to the stomach …”
Section: Clinical Questions and Statementsmentioning
confidence: 99%
“…Because POEM is carried out from inside the esophagus, it is more difficult to determine whether the surgery is being done on the gastric side, compared with Heller myotomy. As a result of this, the techniques below are used to verify that the surgery is proceeding on the gastric side . The double‐scope method is particularly useful because it allows direct vision to verify that the myotomy extends down to the stomach …”
Section: Clinical Questions and Statementsmentioning
confidence: 99%
“…Depending on the orientation of the submucosal tunnel, it was possible to observe a part of the oblique muscle and the large branch of the left gastric artery in some patients, indicating that the scope was within the lesser curvature of the stomach. 24 Endoscope resistance: When creating the submucosal tunnel, it is possible to note the narrowing of the esophageal lumen closer to the LES, which then opens wide into the stomach. When the endoscope is inserted into the stomach cavity after the myotomy is completed, it is possible to feel decreased resistance at the LES.…”
Section: Injection Methods 9 : Indocyanine Green Solution Wasmentioning
confidence: 99%
“…35 One of the problems during POEM is ensuring the appropriate length of myotomy on the gastric side. Tanaka et al 36 reported that the two penetrating vessels in the gastric cardia are a simple and reliable indicator of the appropriate distal end of myotomy. In addition, prevention of gastroesophageal reflux (GER) after POEM is also an issue, and Inoue et al 37 reported POEM+F in which endoscopic fundoplication is performed after POEM.…”
Section: Current Status Of Therapeutic Endoscopy For Gastric Lesionsmentioning
confidence: 99%